Sustainability of different cropping systems under varying sowing dates in Marathwada region: SUSTAINABILITY OF DIFFERENT CROPPING SYSTEMS UNDER VARYING SOWING DATES - D N GOKHALE; V V DHAIPAHALE; V M BHALE; G L SAWARGAONKAR (Journal of Oilseeds Research, 2013)
The field experiments were carried out at Instructional Farm, AICRP on Dry land Agriculture, Marathwada Agricultural University, Parbhani during the rainy season of 2001-2005 on eight different cropping systems consisting of important food, pulse and oilseed crops of Marathwada region under varied weather conditions. The resultsrevealed that intercropping of sorghum (CSH-9)+ pigeonpea, pear millet + pigeonpea and castor + soybean sown in 26 meteorological week (MW) produced the highest grain yield and average productivity of the system during all the years of experimentation as compared to rest of the cropping systems. Similarly, castor + soybean produced the highest sorghum grain equivalent which was at par with soybean + pigeonpea, Arborium cotton + soybean and cotton (NHH-44) + soybean. The sowing of all the crops and cropping systems on 26 MW recorded significantly highestsustainable yield index (0.52) as compared to sowing of all cropping systems on delayed sowing dates.